Resurfacing the Great Toe by an Island Flap - Mrinmoy Nandi; Siti Roy Chowdhury (Indian Journal of Plastic Surgery)
A distally based dorsalis pedis island flap has been used to resurface the soft tissue defects of the great toe successfully in five cases.